Early clinical evaluation of the intranasal TLR7 agonist GSK2245035: Use of translational biomarkers to guide dosing and confirm target engagement. Issue 4 (4th August 2015) - Tsitoura, D; Ambery, C; Price, M; Powley, W; Garthside, S; Biggadike, K; Quint, D
Abstract : Modulation of the airways' immune milieu is a key therapeutic goal for remission from respiratory allergies. To explore this hypothesis, GSK2245035, a selective Toll‐like receptor 7 (TLR7) agonist with preferential Type‐1 interferon (IFN)‐stimulating properties, was developed for intranasal application. Doses for clinical assessment were extrapolated from translational biomarker studies in primates. Randomized, double‐blind, placebo‐controlled trials in healthy volunteers and patients with allergic rhinitis demonstrated that intranasal GSK2245035 doses <100 ng were tolerated and did not cause nasal inflammation. Higher doses were not tested due to considerable cytokine release syndrome‐related symptoms observed at 100 ng. Clear target engagement, reflected by local and peripheral increase of IFN‐gamma‐inducible protein‐10, was observed at 20 ng, indicating IFN‐stimulated immune changes at tolerated doses. Repeat intranasal administration at weekly intervals did not tolerize or amplify the pharmacological response. Intranasal GSK2245035 has an acceptable safety profile at doses that induce local TLR7‐mediated immune responses.